(untitled) (Revista Espinhaço, 2022)
The study aimed to know some sociocultural traditions of the quilombola communities and also to know and to list foods and remedies from animals with their respective uses in health treatments. e communities surveyed are located in Serra do Espinhaço Meridional, in Diamantina (Minas Gerais, Brazil). Data collection was carried out through anthropological data, observations, records and characterization of natural and faunal resources with therapeutic potential, and also throughinterviews, seeking to identify ways of using local products. We evidenced phenomena of resignification of nature and socioenvironmental and cultural interaction, expressed in traditional practices that characterize these communities. ese practices can be thought as techniques in a broader sense, as advocated in studies by Milton Santos. Communities are ethnically constituted maintaining the collective memory of the group, thus forging a tradition that incorporates innovations; although they present daily difficulties derived from the contrast between social isolation in rural areas and at the same time the presence of visitors from large urban areas. We show that the communities studied have a traditional and popular culture where they express their ethniccultural identities, so that the therapeutic practices/techniques presented here can be thought of as intangible cultural heritage, especially knowledge and practices, which leads to elaborating the constitution of space that is guided by the relationship between nature and society.